Escherichia coli strains of phylogenetic group B2 and D and bacteriocin production are associated with advanced colorectal neoplasia - Kohoutova, Darina; Smajs, David; Moravkova, Paula; Cyrany, Jiri; Moravkova, Monika; Forstlova, Miroslava; Cihak, Michal; Rejchrt, Stanislav; Bures, Jan (BMC infectious diseases, 2014)
BACKGROUND: Colorectal cancer (CRC) is the 3rd most common cancer worldwide and the Czech Republic has the 6th highest incidence of CRC worldwide. Large intestinal microbiota play in its etiopathogenesis important role. Bacteriocins are proteins, produced by bacteria from the Enterobacteriaceae family. The aim of our prospective study was to assess the colonization of large intestinal mucosa by Escherichia coli strains and to investigate their bacteriocin production. METHODS: A total of 30 consecutive patients with colorectal adenoma, CRA (17 men, 13 women, aged 39-79, mean age 63 ± 9), 30 patients with CRC (23 men, 7 women, aged 38-86, mean age 67 ± 11) and 20 healthy controls (9 men, 11 women, age 23-84, mean age 55 ± 15) were enrolled into prospective study. Mucosal biopsies were taken in the caecum, transverse colon and rectum during pancolonoscopy. Microbiological culture, isolation and identification of bacteria followed. Bacteriocin production was assessed by growth inhibition of indicator strains E. coli K12-Row, E. coli C6 (phi), and Shigella sonnei 17. Identification of bacteriocin-encoding determinants and E. coli phylogroups was performed using PCR methods. RESULTS: A total of 622 strains were isolated and further investigated. A significantly higher frequency of simultaneous production of colicins and microcins was revealed in the group of patients with CRC, when compared to patients with CRA, p = 0.031. A significantly higher frequency of E. coli phylogroup D was found in patients with CRC, when compared to controls, p = 0.044. A significantly higher prevalence of bacteriocinogeny was confirmed in patients with advanced adenoma when compared to patients with non-advanced adenoma, p = 0.010. Increasing bacteriocinogeny was associated with an increasing stage of CRC (assessed according to TNM classification). Either E. coli phylogroup B2 or E. coli phylogroup D were isolated in biopsies of patients with right-sided CRC. A statistically higher incidence of E. coli phylogroup B2 was found in patients with right-sided CRC when compared to patients with left-sided CRC, p = 0.028. CONCLUSIONS: Large intestinal mucosa of patients with more advanced colorectal neoplasia is colonized with more virulent strains of E. coli and higher production of bacteriocins is observed in these patients when compared to those with less advanced colorectal neoplasia.
Keywords: Adenocarcinoma; kolon; Humans; Case-Control Studies; Phylogeny; lidé středního věku; studie případů a kontrol; mikrobiota; koliciny; Female; Aged; dospělí; Escherichia coli; Microbiota; senioři; lidé; Colon; Colicins; Adult; ženské pohlaví; kolorektální nádory; Male; Middle Aged; fylogeneze; Bacteriocins; Czech Republic; Aged, 80 and over; adenom; Adenoma; senioři nad 80 let; adenokarcinom; Česká republika; mužské pohlaví; prospektivní studie; Colorectal Neoplasms; bakteriociny; Prospective Studies